Gravity map of the Isla Grande de Tierra del Fuego, and morphology of Lago Fagnano - Lodolo, Emanuele (2007)
A complete Bouguer gravity map of the central-eastern part of the Isla Grande de Tierra del Fuego, and a general bathymetric chart of the Lago Fagnano have been realized, on the basis of a series of field geophysical surveys carried out on the Island since 1998. The regional gravity anomaly trend onshore shows a progressive negative gradient from N to S. Distinct, broadly E-W-trending gravity minima are superimposed on this regional negative gradient. They follow the main trace of the Magallanes-Fagnano fault system, which represents the western segment of the left-lateral South America-Scotia transform plate boundary. The gravity minima reflect the presence in the subsurface of restricted and elongated basins developed within the principal displacement zone of the fault system. A relative positive gravity maximum is located just at the SE corner of the Lago Fagnano, and represents the response of a partially exposed crystalline body, occupying an area 3 x 3 km wide. A 2D vertical crustal model has been constructed, combining gravity data inversion and geological information available for the central-eastern region of Lago Fagnano. The bathymetric map of the Lago Fagnano delineates the main morphological features of this 110-km-long, 7-km-wide lake, the largest of Isla Grande. The floor is divided into distinct parts, which suggests that the basin is composed of different sub-basins. In most areas, the basin floor is highly asymmetric in shape, with flat depocentral areas. The most pronounced asymmetry of the basin is seen in the eastern end of the lake, where there is also the deepest depression. The steeper slope of the basin, along the northern shore of the Lago Fagnano, also coincides with the most pronounced regional topographic gradient. The general gravimetric and morphological features of the investigated region are here discussed.